Bacteria : The Benign, the Bad, and the Beautiful - Wassenaar, Trudy M. (Hoboken, N.J. : Wiley-Blackwell, 2012)
"This book introduces bacteria and basic microbiological concepts to readers without previous background in the subject. Each chapter concentrates on a particular topic and can be read in isolation or as part of the whole, and wherever possible points are illustrated through real-world examples and short stories. Although bacterial scientific names are used and translated when possible, in general scientific jargon is avoided in order to make the material as accessible as possible for the lay reader"--
Frontmatter -- Color Plates -- The Blue Planet -- Tree of Life: Let Three Live -- How Old are they? -- On the Move -- Needles -- Dead or Alive -- Nobel Works -- Bacteria and Insects -- Bacterial Toxins -- Enzymes -- Genetics and Genomics -- Antibiotics and Resistance -- Marine Microbiology -- Bacteria and Oil -- Extreme Life -- Record Holders -- Bacteria and Art -- Fixing the Air -- Pest and Pestilence -- Our Bacteria -- Sensing Bacteria -- Bacteria and Mankind -- Big Questions on Small Subjects -- Synthetic Biology -- Bacteria, the Earth, and beyond -- Glossary -- Bibliography -- Index of Bacterial Genera and Species -- Subject Index.
Includes index.
Includes bibliographical references and indexes.
Print version record.
Keywords: Bacteria; Bacteria -- Ecology; Microbiology; Bacteria; Medicine; SCIENCE -- Life Sciences -- Biology -- Microbiology; Bacteria; Bacteria -- Ecology; Microbiology; Electronic books; Electronic books